2014
DOI: 10.1016/j.ijscr.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Perforated diverticulitis of the sigmoid colon causing a subcutaneous emphysema

Abstract: INTRODUCTIONAlthough diverticular disease of the colon is frequent, perforated diverticulitis causing subcutaneous emphysema is a uncommon entity. We wish to present this extremely rare case of perforated colonic diverticulum in the subcutaneous tissue, which is the first one that we have encountered in our practice, along with the accompanying diagnostic and therapeutic issues and a review of the literature.PRESENTATION OF CASEWe report the case of an 83-year-old man who admitted to the emergency room due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Colonic diverticula are small mucosal herniations through points of reduced resistance in the muscular wall of the colon. At these locations, arterioles penetrate the colonic wall which is overgrown with fat tissue [ 1 ]. Colonic diverticula affect people over 50 years of age and constitute one of the most common human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Colonic diverticula are small mucosal herniations through points of reduced resistance in the muscular wall of the colon. At these locations, arterioles penetrate the colonic wall which is overgrown with fat tissue [ 1 ]. Colonic diverticula affect people over 50 years of age and constitute one of the most common human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The most common complication of colonic diverticulosis is acute diverticulitis. The disease is usually silent and must be suspected in patients presenting with crampy abdominal pain, altered bowel habits, anemia, chronic abdominal pain or discomfort [3] .…”
Section: Discussionmentioning
confidence: 99%
“…However, it can also appear with nontypical signs, through complications such as chronic abscesses, the creation of fistulae, and bowel obstruction. Therefore, cases have been reported that presented with colovesical and colovaginal fistulae [ 6 ], perianal fistulae [ 7 ], abscess formation on the abdominal wall [ 1 ], the thigh [ 6 ], or the renal fossa during end-stage renal disease [ 8 ], subcutaneous emphysema [ 9 ], and a perforation in a lumbar hernia [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal CT is the imaging examination of choice, as it sets the definite diagnosis, shows the extent of abdominal inflammation, and excludes any other causes of acute abdominal pain [ 9 ]. In our case, a CT was immediately performed after the lumbar abscess drainage because, in combination with the abdominal pain, the X-ray findings, and the medical history, a clinical suspicion of diverticular perforation was set.…”
Section: Discussionmentioning
confidence: 99%